Development of ZrO2-TiO2 binary nanocomposites for enhanced energy storage in supercapacitors - Sridevi Patil; Bipin S. Chikkatti; Ashok M. Sajjan; Nagaraj R. Banapurmath (Discover Electrochemistry)
Abstract This study focuses on the development of ZrO₂–TiO₂ binary nanocomposites for use in supercapacitor applications. The functionality of the nanoparticles is examined through Fourier transform infrared spectroscopy, X-ray diffraction while their surface morphology is analyzed using scanning electron microscopy. Electrochemical performance is evaluated using techniques such as Cyclic Voltammetry, Electrochemical Impedance Spectroscopy, and Galvanostatic Charge–Discharge measurements. The ZrO₂/TiO₂ nanocomposite demonstrates a high specific capacitance of 226.5 F g⁻1 at a current density of 0.75 A g⁻1. It also exhibits impressive stability, retaining 86% of its capacitance and almost 100% coulombic efficiency after 4000 cycles. Moreover, the nanocomposite exhibits an impressive power density of 5000 W kg⁻1, demonstrating its capability for rapid energy delivery, which is a critical requirement for high-power applications. Simultaneously, it achieves a high energy density of 125.8 Wh kg⁻1, signifying its ability to store substantial amounts of energy per unit mass. Given these remarkable attributes, the ZrO₂–TiO₂ nanocomposite emerges as a highly promising material for energy storage applications, offering a compelling alternative to conventional electrode materials and paving the way for the development of more efficient, sustainable, and high-performance electrochemical energy storage systems. Graphical abstract